Comparison Study on E. coli Inactivation and Physical Changes of Thermal and Non Thermal Processing using PEF (Pulsed Electric Field) in Fresh Milk Pasteurization - Hawa, La Choviya; Susilo, Bambang; Susilo, Bambang; Jayasari, Natalia Eka; Jayasari, Natalia Eka (Jurnal Teknologi Pertanian, 2011)
The objectives of this research were to determine the lethal rate of E. coli and to analyze the density, moisture content, viscosity, boiling point, freezing point, and color changes in non thermal pasteurization (pulsed electric field), thermal pasteurization (heat treatment), and combination of both in fresh milk. Â Experimental-descriptive method with 2 factors was used in this research. First factor was voltage (20, 40, 60, 80 and 100 kV) and second factor was type of pasteurization (non thermal, thermal, and combination thermal-non thermal). Pasteurization time was 60 second and each treatment was replicated three times. The results showed that the highest E. coli inactivation was combination of thermal and non thermal pasteurization i.e 2.5 log cycles. Physical attributtes (density, moisture content, viscosity, boiling point, freezing point, and color) of milk that treated by non thermal pasteurization and combination did not change significantly after pasteurization compared to fresh milk.Keywords: thermal and non thermal pasteurization, lethal rate, physical attributtes